Correlation of Motivation and Value Orientation of Project Managers - ModranskÃ½, RÃ³bert; LajÄin, Daniel (Ital Publication, 2021)
The objective of this paper is to identify the relationship between the dimensions of performance motivation and value preferences of project managers in large companies. To examine the relationship, it was first necessary to find out what the value system of project managers is and what their motivational profile is. The research took the form of a questionnaire survey in large Czech companies, which belong to CZ-NACE C. Standardized questionnaires were used for data collection. The PVQ questionnaire was used to determine the value system and the LMI questionnaire was used to determine the motivational profile. Data were evaluated by using descriptive statistics and relationships were evaluated by using Person's correlation coefficient. Student's t-test was used to verify statistical significance. It was found that the analyzed values in the set of respondents are almost the same, all analyzed values are perceived by the respondents as significant. The most represented value among the respondents is benevolence and the least represented is tradition. We identified identical findings in the case of analysis of performance motivation. Of the four dimensions of motivation examined, the project managers addressed confidence in success to be the most important. A statistically significant relationship was found between commitment and power and success, between flexibility and stimulation, universalism and benevolence, between self-control and power, success, conformity and safety, and between confidence in success and power, success and stimulation.Â Doi: 10.28991/esj-2021-01282 Full Text: PDF